Osteoblast, ﬁbroblast and in vivo biological response to poly(vinylidene ﬂuoride) based composite materials - Costa, R (2013)
Electroactivematerials can be taken to advantage for the development of sensors and actuators as well as for novel tissue engineering strategies. Composites based on poly(vinylideneﬂuoride),PVDF,have been evaluated with respect to their biological response. Cell viability and proliferation were performed in vitro both with Mesenchymal Stem Cells differentiated to osteoblasts and Human Fibroblast Foreskin 1. In vivo tests were also performed using 6-week-old C57Bl/6 mice. It was concluded that zeolite and clay composites are biocompatible materials promoting cell response and not showing in vivo pro-inﬂammatory effects which renders both of them attractive for biological applications and tissue engineering, opening interesting perspectives to development of scaffolds from these composites. Ferrite and silver nanoparticle composites decrease osteoblast cell viability and carbon nanotubes decrease ﬁbroblast viability. Further, carbon nanotube composites result in a signiﬁcant increase in local vascularization accompanied an increase of inﬂammatory markers after implantation.